Biomass yield, nutritional composition, preservation techniques of Moringa oleifera, and the effect of M. oleifera silage on the milk production and quality of local Red Chittagong cattle - Islam, Md Tarequl; Sultana, Nasrin; Bashar, Muhammad Khairul; Miah, Manik; Hasan, Md. Shamim (Frontiers in Animal Science, 2024)
This experiment aimed to evaluate the biomass yield, nutritional composition, preservation techniques of Moringa oleifera, and the effect of M. oleifera silage on the milk production and quality of local Red Chittagong cattle (RCC). Four varieties of M. oleifera were planted, cultivated, and harvested on the Bangladesh Livestock Research Institute (BLRI) research farm. The findings revealed the highest biomass yield in Paraynal varieties (11.24 ± 0.41 tons/ha/year) compared to others. The maximum DM percentage was found in PKM-2 (21.85 ± 1.65) followed by the PKM-1 (21.38 ± 1.98), Paraynal (20.17 ± 2.35), and Black (17.81 ± 1.28) varieties. The study observed greater crude protein (CP) percentage in Black varieties (18.07 ± 0.18) compared to other varieties. A feeding trial was conducted on 10 RCC native dairy cows. Two groups were considered: one was the control (T0) group fed the German grass and concentrate mixture, and the other was the treatment (T1) group fed the moringa silage and concentrate mixture. Each group consisted of five lactating RCC. Moringa oleifera was collected from the BLRI research farm and chopped for silage preparation. The pH of moringa silage was 4.07 ± 0.02, which ensured good quality. There was no significant difference in total DM intake, but the total CP intake (0.55 kg/day) was significantly higher in the control group and the total ME intake was significantly higher in the treatment group compared to the other group. The T1 group increased milk yield by approximately 14.2%. Milk composition was not significantly (P > 0.05) different between the two groups, whereas milk fat significantly differed. Milk fat was slightly higher in the T1 group and the difference between the groups was 0.46%. Moringa silage increased PUFA, linoleic acid (C18:2), linolenic acid (C18:3), arachidonic acid (C20:0), and eicosapentaenoic acid (C20:1) and decreased SFA and MUFA in milk. It was concluded that moringa silage feeding will be a good source of nutrients for livestock to maintain their good health and productivity.